TI_GERICHTE 12.2019.69 vom 8. Oktober 2020 , Responsabilità per attività medica - violazione dell'obbligo di diligenza - TI Tribunale d'appello (2020)
Responsabilità per attività medica - violazione dell'obbligo di diligenza